Reformulasi Rumusan Sanksi Pidana Mati dalam Undang-Undang Nomor 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi - Dewa Gede Agung Oka Danurdara; Ade Adhari (CV Rewang Rencang, 2024)
This research aims to examine and analyze the death penalty sanction in the law on the eradication of corruption against the perpetrators of corruption in Indonesia today and criminal sanctions in the future, which aims to increase efforts to prevent and eradicate corruption. The method used in this research uses a normative juridical approach, which focuses on looking at applicable legal standards. The results of this study indicate that the death penalty against perpetrators of corruption in Indonesia is regulated in Article 2 paragraph (2) of Law Number 31 of 1999 concerning Eradication of Corruption Crimes which states that a person who commits corruption can be sentenced to death if the elements are accompanied by certain circumstances. The death penalty arrangement needs to be explicitly regulated again in a reform of the legislation so as not to cause uncertain interpretations in making a decision in sentencing suspected perpetrators of corruption. The need to make comparisons with other countries in the preparation of a regulation in order to produce a new regulation regarding the eradication of corruption is in accordance with what is expected both among law enforcers and in society. Future policies must consider the quality and amount of corruption as an indicator of the imposition of the death penalty.